2013
DOI: 10.1111/j.1740-8784.2012.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

The CEO's Representation of Demands and the Corporation's Response to External Pressures: Do Politically Affiliated Firms Donate More?

Abstract: This study seeks to explain why firms respond in different ways to similar external administrative pressures, such as government demands for charitable giving, particularly in a transitional economy such as China's. Taking the perspective of the CEO's representation on external demands, the study explores the relationship between political affiliation and corporate giving, stimulated by powerful and politically affiliated CEOs, who are the government's natural constituency and who comply with governmental dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 77 publications
(142 reference statements)
1
43
0
Order By: Relevance
“…Second, cash holdings have strategic benefits that can be used by firms to engage in philanthropic giving for forging social exchanges with officials. For example, corporate social responsibility received considerable attention after the Wenchuan earthquake in 2008 (Jia and Zhang, ). However, our study finds that, beginning in 2001, philanthropic giving has helped privately owned firms survive during an even longer period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, cash holdings have strategic benefits that can be used by firms to engage in philanthropic giving for forging social exchanges with officials. For example, corporate social responsibility received considerable attention after the Wenchuan earthquake in 2008 (Jia and Zhang, ). However, our study finds that, beginning in 2001, philanthropic giving has helped privately owned firms survive during an even longer period.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with Brown et al (), Jia and Zhang (), and Wang and Qian (), we measure philanthropic giving at firm i headquartered in city j during year t . Giving is the log‐transformed ratio of philanthropic giving to total assets ( ratio of giving to assets ×100+1).…”
Section: Data and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, research has shown that firms with strong affiliation with politicians tend to donate more (Jia & Zhang, 2013). This suggests that government-encouraged donation may be a creative form of bribery.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 95%
“…Further, firms may give due to political pressure when the CEO has strong government affiliation (Jia & Zhang, 2013) regardless of the CEO's or chairperson's motive. First, we examine political appointment as a means of fulfilling pro-social motives.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%